2018
DOI: 10.1145/3209960
|View full text |Cite
|
Sign up to set email alerts
|

Is Virtual Citizen Science A Game?

Abstract: The use of game elements within virtual citizen science is increasingly common, promising to bring increased user activity, motivation and engagement to large-scale scientific projects. However there is an ongoing debate about whether or not gamifying systems such as these is actually an effective means by which to increase motivation and engagement in the long term. While gamification itself is receiving a large amount of attention, there has been little beyond individual studies to assess its suitability or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Gamification is viewed as a powerful design technique that has the ability to improve user experience and transform mundane, repetitive tasks into engaging experiences (Franzoni & Sauermann, 2014), thereby motivating and retaining participants (Bowser et al, 2013;Bowser et al, 2014;Iacovides et al, 2013;Pedersen et al, 2017). Such game elements include for example rewards, online gaming badges, leaderboards, or competitions (Simperl et al, 2018). Gamification may encourage people to take part in a project or help to sustain engagement, or both (Rotman et al, 2012;Simperl et al, 2018).…”
Section: (D) Game Elements As Additional Incentivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gamification is viewed as a powerful design technique that has the ability to improve user experience and transform mundane, repetitive tasks into engaging experiences (Franzoni & Sauermann, 2014), thereby motivating and retaining participants (Bowser et al, 2013;Bowser et al, 2014;Iacovides et al, 2013;Pedersen et al, 2017). Such game elements include for example rewards, online gaming badges, leaderboards, or competitions (Simperl et al, 2018). Gamification may encourage people to take part in a project or help to sustain engagement, or both (Rotman et al, 2012;Simperl et al, 2018).…”
Section: (D) Game Elements As Additional Incentivesmentioning
confidence: 99%
“…Such game elements include for example rewards, online gaming badges, leaderboards, or competitions (Simperl et al, 2018). Gamification may encourage people to take part in a project or help to sustain engagement, or both (Rotman et al, 2012;Simperl et al, 2018). Similarly, communication tools and community elements may help to sustain engagement over time, by allowing participants to interact through recognizing their achievements as meaningful (Iacovides et al, 2013;Tinati et al, 2016).…”
Section: (D) Game Elements As Additional Incentivesmentioning
confidence: 99%
“…In Table 1, it can be observed that more than 80% of users belong to the first group and also covered a total of 1,492 of the images analyzed, which represents 70% of the total. These indicators reflect, although it is not relevant in the validation of the method, that most users leave the experiment promptly, after few executions, mainly because the experiment needs to be improved to be more attractive to users, through gamification techniques that motivate or reward them, as proposed by [37] [38].…”
Section: B Second Approach: Integrating a Reputation Systemmentioning
confidence: 99%
“…Simultaneously looking at the quality of the collected data has received less attention (Budde et al, 2017a;Simperl, Reeves, Phethean, Lynes, and Tinati, 2018). Prestopnik, Crowston, and Wang (2014) showed that games with a purpose can in principle yield contributions of equal quality.…”
Section: Related Workmentioning
confidence: 99%